Ethics in Management Research and Artificial Intelligence - Daniela M. Salvioni; Alex Almici (Symphonya)
Artificial intelligence (AI) is one of the most important and transformative technologies of our time, with potential applications in the field of scientific research. The advancement of management studies can benefit from the adoption of tools and methodologies based on AI. In this article, we argue that the use of AI-based tools for the development of scientific contributions in the field of management studies entails opportunities but also risks in the absence of an ethical approach, closely related to the intention to offer effective contributions to scientific advancement.